Strategy to Increase Public Awareness in Flood-Prone Areas - Londa, Very Yohanis; Dengo, Salmin (Universitas Padjadjaran, 2025)
Floods are one of the most frequent natural disasters in Indonesia and have a wide impact on social, economic, and environmental life. In Manado, continuously from 2024, there are 10 sub-districts and 48 villages that are categorized as flood-prone areas. This study purposed to analyze strategies for increasing public awareness in flood-prone areas in Manado City, North Sulawesi Province. This study applied a qualitative method with a case study approach. Data collection techniques were conducted through in-depth interviews with the Regional Disaster Management Agency of North Sulawesi Province and Manado, and communities in flood-prone locations, direct observation, and secondary data collection. Data analysis was conducted inductively with the stages of reduction, data presentation, interpretation, and conclusion. The results of the study showed that the strategy of socialization and training through print and electronic media was not yet effective. More relevant and targeted strategies include the formation and training of disaster-aware communities at the village level, direct face-to-face socialization, and taking action against community activities that can trigger flooding. These strategies are considered capable of increasing public awareness and preparedness in dealing with disasters, particularly floods.